Microwave-Assisted Efficient Synthesis of Spiropyridine Derivatives via Catalyst- and Solvent-Free One Pot Four Component Reaction - Bhuyan, Debajyoti (Asian Journal of Chemistry, 2020)
A microwave-assisted, one-pot four-component reaction strategy has been developed for the synthesis of some novel spiropyridine derivatives from 1,3-dimethyl barbituric acid, chalcone, aromatic aldehyde and ammonium acetate under catalyst- and solvent-free conditions.